The Chromosome-level genome of Aesculus wilsonii provides new insights into terpenoid biosynthesis and Aesculus evolution - Ye, Lichun; Yang, Lulu; Wang, Bo; Chen, Gang; Jiang, Liping; Hu, Zhigang; Shi, Zhaohua; Liu, Yifei; Chen, Shilin (Frontiers in Plant Science, 2022)
Aesculus L. (buckeye and horse chestnut) are woody plant species with important horticultural and medicinal values. Aesculus seeds are widely used as biomedicine and cosmetic ingredients due to their saponins. We report a chromosomal-scale genome of Aesculus wilsonii. Sequences amounting to a total of 579.01 Mb were assembled into 20 chromosomes. More than half of the genome (54.46%) were annotated as repetitive sequences, and 46,914 protein-coding genes were predicted. In addition to the widespread gamma event with core eudicots, a unique whole-genome duplication (WGD) event (17.69 Mya) occurred in Aesculus after buckeye differentiated from longan. Due to WGD events and tandem duplications, the related synthetic genes of triterpene saponins unique to Aesculus increased significantly. Combined with transcriptome characterization, the study preliminarily resolved the biosynthetic pathway of triterpenoid saponins like aescin in A. wilsonii genome. Analyses of the resequencing of 104 buckeye accessions revealed clear relationship between the geographic distribution and genetic differentiation of buckeye trees in China. We found that the buckeye species found in southern Shaanxi is A. wilsonii rather than A. chinensis. Population dynamics analysis further suggests that the population size and evolution of existing buckeye species have been influenced by climate fluctuations during the Pleistocene and recent domestication events. The genome of A. wilsonii and population genomics of Aesculus provide a resource for future research on Hippocastanaceae. These findings will contribute to the utilization and diversity protection of Aesculus.